Synergistic effects during the co-pyrolysis and co-gasification of high volatile bituminous coal with microalgae. (15th May 2018) - Fermoso, J.; Corbet, T.; Ferrara, F.; Pettinau, A.; Maggio, E.; Sanna, A.
Highlights: Synergistic effects between the two fuels during their co-pyrolysis process were identified. Ash removal (>90%) can potentially reduce operational issues linked to Cl and Na. Synergistic effect during co-gasification at 850–900 °C were evidenced. Na in NM promoted coal char gasification with Ea decrease from 189.9 to 146.1 kJ/mol. Abstract: In this work, the co-pyrolysis and co-gasification of Nannochloropsis sp. microalgae (NM) and Colombian bituminous coal (CC) were performed in order to evaluate potential synergistic effects and the kinetic parameters, which are essential for advancing the co-utilization. The effect of the share of feedstock, microalgae and coal, on the co-pyrolysis and co-gasification behavior was studied under different heating rates and temperatures. There were synergistic effects between the two fuels during their co-pyrolysis process, especially for that mixture containing 50 wt% of microalgae. At conversion levels < 25 wt%, the activation energy ( Ea ) was found to be lower than the individual microalgae, 143 and 170 kJ/mol, respectively. Despite the acid leaching pre-treatment (NM-ac) showed a positive effect on the microalgae pyrolysis kinetics for conversion values < 60 wt%, the trend was inverted at higher conversions, due to the removal of alkali species form microalgae ash, which also slowed the CC/NM gasification. However, ash removal can potentially reduce operational issues related to presence of Cl and Na. Both synergistic and inhibiting effects were observed in the co-gasification experiments. Synergistic effect at temperatures higher than 800 °C was due to the microalgae high Na content that promoted coal char gasification, resulting in an Ea decrease for the coal from 189.9 to 146.1 kJ/mol. This reduction was higher to that expected if both fuels would behave according to the mixtures additive law (159.1 kJ/mol), Inhibiting effect at 750–800 °C can be linked to lower presence of Na on char surface and lower transformation of NaCl in gasification active species.